Textual Researching the Versions of Jiao Yao Xu Lun and Sketching the Relation Between Tu Hua Jiao Yao Xu Lun and Fang Yan Jiao Yao Xu Lun - ZHANG Cuicui, (Journal of Research for Christianity in China (JRCC), 2025)
There are some doubts that Fang Hao insists the book of Jiao Yao Xu Lun hasn’t been published in 1669.By comparing the different versions of Jiao Yao Xu Lun, you can find that the publisher that may adjusts the contant with the development of the times plays an important role in the process of republishing.The two versions in Shanghai dialect, Tu Hua Jiao Yao Xu Lun and Fang Yan Jiao Yao Xu Lun which has been involved in the books of Fang Hao and Louis Pfister, are very different. Fang Yan Jiao Yao Xu Lun adapts from Tu Hua Jiao Yao Xu Lun which is the earliest version in Shanghai dialect.